Efektivitas Teknik Problem Solving Untuk Meningkatkan Keterampilan Berpikir Kritis (Critical Thinking) Taruna - Susi Diriyanti Novalina; Tiara Sylvia; Liber Tommy Hutabarat (Medan State University, 2021)
One of the factors less successful learning process in the classroom is that lecturers are less innovative in applying learning methods. Lecturers still use the classical method of discussion. For that, a learning innovation is needed by applying problem solving methods. The study used quasi experimental design. The research population is medan aviation polytechnic cadets amounting to 40 cadets consisting of 20 people control group and 20 people experimental group. The data collection techniques used include interviews, observations, questionnaires, and tests. The statistical analysis used is Pearson ProductMoment to test validity, Cronbach'sAlpha to test reliability, Lilliefors to test normality,Levene's to test homogeneity, and t test and to test differences and effectiveness. Based on the results of the difference hypothesis test using independent samples t test,critical thinking ability data shows the value of tcalculated>ttable (3,740 > 1,998) with a level of significance (0.000 < 0.05) and the value of cadet learning results shows the value of tcount>ttable (3,656 > 1.998) with a significance level of less than 0.05 (0.001 < 0.05). Meanwhile, the results of the effectiveness hypothesis test using one sample t test,critical thinking ability data showeda table >ttvalue (5,724 > 2.037) with a significance level of < 0.05 (0.000 < 0.05) and a cadet learning value showing a>ttable t value (6,009 > 2,037) with a significance level (0.000 < 0.05). So, it can be concluded that there is a difference in critical thinking skills and learning outcomes between those who use problem solving methods and those who use discussion methods. Problem solving methods are effective in improving critical thinking skills and learning outcomes.